(untitled) (Web of Teachers: Inderscience Research, 2025)
This research is devoted to the analysis of sanitary standards imposed on agricultural machinery repair buildings and the development of their scientifically based solutions. Regulatory documents and international standards in the research process (SanPiN, GOST, ISO 45001) studied and collected empirical data. The results of the study showed that most existing repair buildings do not fully comply with sanitary standards. In particular, an analysis was given based on the development of scientific and practical measures aimed at increasing the level of compliance with sanitary and hygienic requirements in agricultural machinery repair workshops and workshops, the ventilation system of buildings, the level of lighting, noise and vibration state, as well as international and local regulatory documents on creating favorable sanitary and hygienic conditions for workers. According to the results of the study, it was found that the current norms are associated with the main factors affecting the efficiency of production and the health of workers. The article also put forward recommendations for improving existing sanitary standards. In addition, the study is of practical importance for enterprises, specialists and engineers related to the repair of agricultural machinery, and serves to improve the efficiency of the production process by improving sanitary and hygienic conditions.